A critical inquiry into the hyperreality of digitalization in construction. Issue 7 (3rd July 2021) - Boyd, David
Abstract: The built environment is literally and metaphorically concrete but its creation from conception through design and construction involves many levels of abstraction. This spectrum of activities between concrete and abstract is complex and unexplored in construction but it will be shown that a deep understanding of this is required to make successful buildings in a modern age of digitalization. Abstraction is the simplification of an entity with a degree of generalization of purpose and causality but also used to promote the idealization of the entity. When abstractions are believed to be real then there are conditions of hyperreality. This article unpacks the nature of abstraction in the creation of the built environment through three vignettes of practice; considering: drawings, project planning and building modelling. Abstraction has been key to making buildings but is growing in significance because of building information modelling. The themes of loss of meaning, loss of control and loss of perspective are used to show that digitalization involves creating a dangerous illusion of the connection between data and reality thus creating a problematic hyperreality. This can be avoided by stronger thinking, more openness about abstractions and less exaggeration of their performance.